Calcitonin gene-related peptide is not involved in neuropathic pain induced by partial sciatic nerve ligation in mice. (1st May 2022) - Ishida, Kumiko; Tanaka, Satoshi; Shen, Dandan; Matsui, Shuhei; Fuseya, Satoshi; Shindo, Takayuki; Kawamata, Mikito
Highlights: Spinal αCGRP was not involved in neuropathic pain induced by partial sciatic nerve ligation. The involvement of αCGRP may differ depending on the types and regions of neuropathic pain. Anti-CGRP treatment should be carefully considered in various types of neuropathic pain. Abstract: Background: Optimal neuropathic pain (NeP) therapy has still not been established despite great efforts to develop new strategies for NeP analgesia. One possible target might be calcitonin gene-related peptide (CGRP). This is because the expression of CGRP and its receptors in the dorsal horn of the spinal cord might be associated with the persistence of pain symptoms including symptoms of NeP. We previously developed αCGRP knockout mice, and we aimed in this study to clarify the roles of CGRP in NeP by partial sciatic nerve ligation (PSNL) using the knockout mice. Methods: PSNL was performed in αCGRP knockout mice and wild-type (WT) mice, and spontaneous pain behavior and mechanical and thermal hyperalgesia were evaluated after PSNL. CGRP immunoreactivity (IR) was also observed in the superficial dorsal horn and deep dorsal horn of L4 to L5 segments of the spinal cord in WT mice after PSNL. Results: Spontaneous pain behavior and mechanical and thermal hyperalgesia after PSNL were not different between αCGRP knockout mice and WT mice throughout the observation period. The expression of CGRP-IR was not different between the PSNL model and the sham operation model at 1 day and 7 days after surgery. Conclusion: The results suggest that the involvement of αCGRP may differ depending on the type and site of nerve injury, and clinical indications for anti-CGRP treatment of NeP should be carefully based on various pathophysiological conditions of NeP.